Single-Cell ID-seq Reveals Dynamic BMP Pathway Activation Upstream of the MAF/MAFB-Program in Epidermal Differentiation - van Eijl, Roderick A.P.M.; van Buggenum, Jessie A.G.L.; Tanis, Sabine E.J.; Hendriks, Joost; Mulder, Klaas W. (iScience, 2018)
Epidermal homeostasis requires balanced and coordinated adult stem cell renewal and differentiation. These processes are controlled by both extracellular signaling and by cell intrinsic transcription regulatory networks, yet how these control mechanisms are integrated to achieve this is unclear. Here, we developed single-cell Immuno-Detection by sequencing (scID-seq) and simultaneously measured 69 proteins (including 34 phosphorylated epitopes) at single-cell resolution to study the activation state of signaling pathways during human epidermal differentiation. Computational pseudo-timing inference revealed dynamic activation of the JAK-STAT, WNT, and BMP pathways along the epidermal differentiation trajectory. We found that during differentiation, cells start producing BMP2-ligands and activate the canonical intracellular effectors SMAD1/5/9. Mechanistically, the BMP pathway is responsible for activating the MAF/MAFB/ZNF750 transcription factor network to drive late-stage epidermal differentiation. Our work indicates that incorporating signaling pathway activation into this transcription regulatory network enables coordination of transcription programs during epidermal differentiation.